Emigrate to live, Serve to Immigrate. American and Colombian Immigration Legislation for Jews between 1880 and 1930 (2014)
This article takes a look at the treatment given to migrant Jews from Asia to America and Colombia between 1880 and 1930, mainly based on the laws that were created. This legal context, accompanied by a reference to the discussion on the issue of race tha